2020
DOI: 10.1074/jbc.ra120.012575
|View full text |Cite
|
Sign up to set email alerts
|

The ER-associated protease Ste24 prevents N-terminal signal peptide-independent translocation into the endoplasmic reticulum in Saccharomyces cerevisiae

Abstract: Soluble proteins destined for the secretory pathway contain an N-terminal signal peptide that induces their translocation into the endoplasmic reticulum (ER). The importance of N-terminal signal peptides for ER translocation has been extensively examined over the past few decades. However, in the budding yeast Saccharomyces cerevisiae, a few proteins devoid of a signal peptide are still translocated into the ER and then N-glycosylated. Using signal peptide–truncated reporter proteins, we herein report detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Conceptually, in a clogged translocon, substrate likely engages the translocon in an erroneous way, which may leave a conformational “mark” for Ste24 recognition. Consistent with this hypothesis, a recent study showed that in budding yeast, Ste24 prevents inappropriate engagement of the translocon with substrates lacking signal sequence, which may otherwise generate a clogging-like state ( Hosomi et al, 2020 ).…”
Section: Translocon Declogging During Posttranslational Translocationmentioning
confidence: 80%
“…Conceptually, in a clogged translocon, substrate likely engages the translocon in an erroneous way, which may leave a conformational “mark” for Ste24 recognition. Consistent with this hypothesis, a recent study showed that in budding yeast, Ste24 prevents inappropriate engagement of the translocon with substrates lacking signal sequence, which may otherwise generate a clogging-like state ( Hosomi et al, 2020 ).…”
Section: Translocon Declogging During Posttranslational Translocationmentioning
confidence: 80%
“…membrane protein topology, and secretion of proteins lacking signal sequences [38][39][40][41][42][43]. A role in protection against enveloped viruses has also been reported for ZMPSTE24 in mammalian cells [44,45].…”
Section: Plos Onementioning
confidence: 80%
“…However only farnesylated prelamin A peptides exclusively give rise to correctly processed cleavage products [21,55], indicating that farnesylation is important for cleavage fidelity. It is worthwhile noting that ZMPSTE24 and its yeast counterpart Ste24 have been genetically implicated in proteolytic roles in addition to cleavage of farnesylated prelamin A and a-factor, involving still undefined degradative roles in protein quality control and protein translocation and secretion [38,39,41,43]. Furthermore in vitro studies have shown that non-farnesylated peptides unrelated to afactor or prelamin A can also be cleaved by membrane preparations containing Ste24 [56], but little is known about how or whether this latter finding relates to Ste24's still ill-defined in vivo degradative functions in addition to its specific role in a-factor maturation.…”
Section: A?mentioning
confidence: 99%
“…The farnesylated a-factor precursor is the sole known specific substrate for Ste24 in yeast. However, genetic studies have suggested additional functions for Ste24 in ERassociated degradation (ERAD), the unfolded protein response (UPR), clearance of clogged translocons, membrane protein topology, and secretion of proteins lacking signal sequences [38][39][40][41][42][43]. A role in protection against enveloped viruses has also been reported for ZMPSTE24 in mammalian cells [44,45].…”
Section: Introductionmentioning
confidence: 99%